Effectiveness of the Online Community Complaint and Information Service (LAPOR MAS BRO) as a Public Service in North Denpasar District - NI MADE, SURYANI; I Made Sumada; Nyoman Diah Utari Dewi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
Improving public service quality can be achieved through effective community aspiration and complaint services, as mandated by Law No. 25 of 2009. In North Denpasar District, the integration of requests and complaints into a unified system is lacking, leading to unresolved issues. The introduction of the Online Community Complaint and Information Service (LAPOR MASBRO) aimed to address this by providing a platform for public submissions and aspirations. However, the service has seen low participation, with many complaints still directed to the sub-district office. This study evaluates LAPOR MASBRO's effectiveness using descriptive qualitative methods and Budiani's theory of effectiveness. Results show the service is ineffective due to low engagement and lack of prominence. Recommendations include enhancing promotion and collaboration with other complaint services.